Collective Rationality, Unanimity and Liberal Ethics - Karni, E. (Review of Economic Studies, 1978)
Journal Article Collective Rationality, Unanimity and Liberal Ethics Get access Edi Karni Edi Karni Tel-Aviv University and University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 571–574, https://doi.org/10.2307/2297258 Published: 01 October 1978 Article history Received: 01 January 1976 Accepted: 01 October 1977 Published: 01 October 1978